INFLUENCE OF INFLATION, INTEREST RATE AND CURRENCY ON COMPOSITE STOCK SHARE PRICE INDEX LISTED IN INDONESIA OF STOCK EXCHANGE JAKARTA - Erwin Budianto, Nurhana Dhea Parlina Abdul Haris (Program Studi Akuntansi, Universitas Kuningan, 2016)
Inflation, interest rate and currency are factors that influence the (IHSG) Composite Stock Share Price Index. Above also explains, if Inflation rates rise then the Composite Stock Share Price Index will go up, but we see that the theory will not be the same forever with the practice or application. For that we intend to see if it was true what was mentioned by the theory. To find out we took Composite Stock Share Price Index data that listed on Indonesia Stock Exchange from the period 1 January 2013 - until 31 December 2015. Then we took the Inflation rate and interest rate data from the period 1 January 2013 - until 31 December 2015. Inflation, interest rate and currency are of economic factors can influence Composite Stock Share Price Index. If the inflation and interest rate more high than before it can impact of Composite Stock Share Price Index. Otherwise, In this study we will examine Composite Stock Share Price Index from the results obtained output of coefficient over than 0.05 as much as 0.306 so the final inflation, interest rate and currency aren’t influence of Composite Stock Share Price.